United Republic of Tanzania : Sixth Review Under the Policy Support Instrument, Second Review Under the Stand-by Credit Facility Arrangement, and Request for Modification of Performance Criteria-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Tanzania. (IMF Staff Country Reports; Country Report ;, 2013)
Tanzania's economic growth continues to be buoyant. The planned monetary policy tightening is aimed at entrenching gradual disinflation. Executive Directors recommend further enhancing the degree of exchange rate flexibility, and the fiscal deficit reduction envisaged in the draft budget is welcomed. Implementation of the structural reform agenda needs to be reinvigorated. Although the medium-term outlook remains strong, short-term risks to the program are foreseen. There is progress in areas including health, higher education enrollment, and revenue collection, but challenges in poverty reduction remain.